Changing Autonomy in Operative Experience Through UK General Surgery Training: A National Cohort Study. Issue 3 (March 2019) - Elsey, Elizabeth J.; Griffiths, Gareth; West, Joe; Humes, David J.
Abstract : Objectives: To determine the operative experience of UK general surgery trainees and assess the changing procedural supervision and acquisition of competency assessments through the course of training. Background: Competency assessment is changing with concepts of trainee autonomy decisions (termed entrustment decisions) being introduced to surgical training. Methods: Data from the Intercollegiate Surgical Curriculum Programme and the eLogbook databases for all UK General Surgery trainees registered from August 1, 2007 who had completed training were used. Total and index procedures (IP) were counted and variation by year of training assessed. Recorded supervision codes and competency assessment outcomes for IPs were assessed by year of training. Results: We identified 311 trainees with complete data. Appendicectomy was the most frequently undertaken IP during first year of training [mean procedures (mp) = 26] and emergency laparotomy during final year of training (mp = 27). The proportion of all IPs recorded as unsupervised increased through training ( P < 0.05) and varied between IPs with 91.2% of appendicectomies (mp = 20), 40.6% of emergency laparotomies (mp = 27), and 17.4% of segmental colectomies (mp = 15) recorded as unsupervised during the final year of training. Acquisition of competency assessments increased through training and varied by IP. Conclusions: The changing autonomy of trainees through the course of an entire training scheme, alongside formal competency assessments, may provide evidence of changing entrustment decisions made by trainers for different key procedures. Other countries utilizing electronic logbooks could adopt similar techniques to further understanding of competency attainment amongst their surgical trainees. Abstract : Supplemental Digital Content is available in the text